Balik Banda! transcriptions of composed heritage pieces for band - Vocalan, Adrian Aaron D.
The Angono Concert Band Inc. has produced a wide collection of marches originally composed for the band by Col. Fulgncio Gragera. However, these pieces were lost in the span of 39 years fur to poor archiving. Fortunately, the band under the leadership of Gragera recorded these marches in a CD and provided the next generation to hear those marches. This project will showcase 6 out of 16 marches in the CD, the arrangements of the 6 marches will be done by the project proponent and be finished hopefully on January 2019. The rehearsals of the pieces will start from February next year and will be handled by the project proponent too. Furthermore, this projectis aimed towards the senior and junior members of the band as they perform these 6 marches in a culminating activity which is intended to happen on May 2019.